The impact of financial development on economic growth: Evidence from OECD countries - Şendoğan, Gülseda (İstanbul Bilgi Üniversitesi, 2020)
ABSTRACT: Financial development is a crucial factor for all countries because it directly affects economic development, which means that it affects every single unit of a country. More than that, financial development is the pillar of a country's independence. This is why it encourages economic growth in terms of capital appreciation, technological progress, production, and investment. Thus, the question of how increasing financial developments in the post-globalization period and, which channels affect economic growth has been a topic that has been explored for a long time. While empirical studies often establish a direct link between indicators that provide financial development and growth, discussions continue on how these results should be interpreted. This study tries to shed light on this relationship with OECD countries. While doing this, the panel data analysis method was used, and the findings obtained as a result of the study show the existence of a significant relationship.

ÖZET: Finansal gelisme direk olarak ulkelerin her birimini etkiledigi icin cok onemli bir faktordur.Ayrica, finansal gelisme bir ulkenin bagimsizliginin temelidir. Bu sebeble, finansal gelisme sermaye artisini, teknolojik ilerlemeyi, uretimi ve yatirimi destekler. Bu nedenle küreselleşme sonrası dönemde artan finansal gelişmelerin nasıl ve hangi kanallardan ekonomik büyümeyi etkilediği sorusu uzun süredir araştırılan bir konu olmakla birlikte araştırmacılar farklı sonuçlar etmesi bu ilişkiye dair araştırmaların artmasını teşvik etmiştir. Ampirik çalışmalar genellikle finansal gelişmeyi sağlayan göstergeler ile büyüme arasında doğrudan bir ilişki kurarken, bu sonuçların nasıl yorumlanması gerektiğine dair tartışmalar devam etmektedir. Bu çalışma, OECD ülkeleri temel alınarak bu ilişkiye ışık tutmaya çalışmaktadır. Bunu yaparken, panel data analizi metodu kullanılmış ve çalışma sonucunda elde edilen bulgular, anlamlı bir ilişki varlığını göstermektedir.
Finansal gelis?imin ekonomik bu?yu?me u?zerindeki etkisi: OECD ülkelerinden kanıtlar
Keywords: OCED Countries; Financial Development; Economic Growth; Random And Fixed Effect; Hausman Test; OECD Ülkeleri; Gelişim; Ekonomik Gelişme; Rastgele Ve Tesadüf Efekt Model